IT Companies: Trends and Outlook - Sazonets, Olga; Vovk, Viktoriia; Sazonets, Igor (<center>Conference Proceedings Determinants Of Regional Development</center>; No 3 (2022): Conference Proceedings - IX International Scientific Conference Determinants of Regional Development, 2022)
The paper aims to explore the income stability of 9 IT companies that are high tech leaders, and to single out the group of the most attractive ones among them. Hence, the authors conducted an analysis of the dynamics of the actual and projected level of the net income. The scholars selected Alphabet, Apple, Cisco System, Microsoft, Dell Technologies, HP Enterprise, IVM, Ericsson, and Huawei for the research. The given study used heuristic analysis, as well as least squares, confidence intervals and clustering, in order to evaluate the companies' performance. The research revealed that Alphabet, Apple, Cisco System, Microsoft Dell Technologies, IVM, and Huawei enjoyed the increasing dynamics of net income, whereas the indicators of HP Enterprise, Ericsson had decreasing dynamics both in actual and forecast values. The paper determined the width of the confidence interval, which certified that Apple, Cisco System, Dell Technologies, and Huawei are the most stable companies. At the same time, Microsoft, HP Enterprise, IVM, and Ericsson experience the highest fluctuations. Simultaneously, the unfavourable position of the HP Enterprise and Ericsson is intensified by the fact that these companies have negative dynamics of the actual value of net income and its forecast. There is a number of reasons for this situation, however the major one is the transfer of capital to other enterprises.